Peran Filsafat Ilmu Dalam Pengembangan Kurikulum Merdeka di Indonesia (International Forum of Researchers and Lecturers, 2024)
In developing an independent curriculum in Indonesia, one of them cannot be separated from the role of philosophy of science, which in curriculum development is the spirit or foundation of education which must be evaluated, studied periodically, innovative and dynamic following changing times, such as the philosophical Ki Hajar Dewantara who stated that education is appropriate. the nature of nature and the nature of the times, meaning that education develops according to the times. Of course, all the changes and developments that occur in the educational curriculum cannot be separated from the results of several studies on how the implementation of this independent curriculum can overcome learning loss, the effects of the Covid pandemic plus the global challenges of change from era 4.0 to Society 5.0, which has the impact that today's generation needs. have the ability to think critically, creatively and innovatively. In the independent curriculum, it can be seen that the superiority of its characteristics is that the material is simpler and more in-depth and there is a significant reduction in material. The materials presented are limited to essential material. Reducing material provides an opportunity for students to explore the material more comprehensively. Next is more independence, which means that in an independent curriculum, students are given more freedom to choose the subjects they are interested in according to their interests, talents, potential and aspirations. Meanwhile, teachers can teach according to the stages of student achievement and development. So it is more relevant and interactive. Students are guided to be able to collaborate, work together to form groups to identify problems that are becoming issues to strengthen the profile of Pancasila students, namely faith and devotion to God Almighty and noble character, global diversity, mutual cooperation, independence, critical reasoning and creativity. The essence of this independent curriculum is independent learning. This aims to enable students to explore their respective interests, potential and talents.